Penerapan Financial Quotient Terhadap Ketahanan Keuangan Pada Toko Retail Sembako Di Kelurahan Wonorejo Kecamatan Rungkut Surabaya - Veren Putri Shamaya; Sabrina Nova Ashara; Arswarani Leonica; Maria Yovita R Pandin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to find out how the application of financial quotient to financial security in the management of a basic food retail business in Wonorejo Village, Rungkut Dis trict. The approach used in this study is a qualitative approach with the interview method as data collection. Based on the research results, it is known that financial quotient supports financial maintenance. The perspective of the success of the basic food retail business is quite good, but there is still a lack of effectiveness in the management of the 4 (four) each of these retail stores. In terms of competitive advantage, informants 3 and 4 tend to have more consumers, in sales activities informants 3 serve more according to the needs sought or retail, so that goods run out faster, while informants 4 sell at wholesale prices so they are cheaper than other stores. So it can be concluded that the financial quotient in the management of 4 food retail store informants has been sufficiently implemented in determining business success and impacting competitive advantage.